Association of inflammatory gene variants with problematic alcohol use in a Colombian population: Genetic variants of inflammation in Colombian alcoholics - Rey Buitrago, Mauricio; Aristizabal Gutierrez, Fabio Ancizar (Cellular and Molecular Biology, 2025)
Alcohol dependence is a multifactorial disease that constitutes a significant public health concern and a significant risk for individual, family, and social health. Its genetic component exhibits significant ethnic variation and is closely associated with the personal evolution of the disease. However, although multiple loci have been identified, no functional variants have been identified. In this work, we selected some genes from the inflammatory response pathway and searched for SNV (single nucleotide variants) in their promoter region that could be associated with the disease. We compared cases of problematic alcohol consumption (n=66) with controls (n=73) in a population sample taken at the National University of Colombia, Bogotá headquarters. Peripheral blood DNA extraction was performed. We used PCR and Sanger sequencing to find 28 SNVs and one STR in 10 inflammatory response genes that are connected to alcoholism. Then, using various bioinformatic tools, the analysis of haplotypes, linkage disequilibrium, epistasis and genetic networks was carried out. Allele and genotypic frequencies for this Colombian population were reported for the first time. Additionally, we found haplotypes that could be protective and risk factors for the disease, and gene interactions that have cumulative effects related to the drinker phenotype. The investigation of haplotypes, gene interaction, and gene networks is a highly effective methodology for identifying potential associations in small samples. Additionally, SNCA, IL-6R1, TNFR1, and MIF genes were profiled for further studies.